Analisis dan Perancangan E-ticket Metaverse Event Berbasis Midtrans Payment Gateway (Studi Kasus: PT Semesta Realitas Indonesia) - Syahputra, Muhammad Dimas Arya; Mulya, Muhamad Femy (Journal of Electrical Power Control and Automation (JEPCA), 2025)
In the modern era like today, the world is experiencing developments in the field of science and technology. Metaverse technology has become a hot topic of discussion around the world, with its ability to create 3D virtual worlds using AR and VR technology where users can appear to interact in a real virtual world. PT. Semesta Realitas Indonesia (Festivo) is now developing a metaverse that can present a new experience in participating in virtual events/festivals. In making the world of metaverse, PT. Semesta Realitas Indonesia (Festivo) requires a website as a promotional media, information center, managing metaverse events and of course for online ticketing transactions. E-ticket transactions use the Midtrans payment gateway to simplify the payment process. In this study using UML for system design and ERD as part of database design. Then use the Agile Scrum method as a method in system development. This website-based application is built using the HTML, CSS, Javascript, and PHP programming languages, and is assisted by the Laravel and Bootstrap frameworks. The results of this study produce a website-based application that has been tested using Black-box testing with a success rate of 90%, which means the system is classified as good. The application can be used by companies as a media to promote metaverse events, and purchase e-tickets with midtrans to enter the world of metaverse events.